New scenarios require reviewing the role of every teacher academic - Cintia Caserotto Miranda (Perspectivas Metodológicas​)
This article provides a brief description — resorting to Sanchez (2013) - of the academic excellence that characterizes the university teacher of the Religious University (eg University Catholic) Next, it is exemplified with a specific case, the reception that academic excellence, in terms raised by Sánchez (2013), obtained in the Argentinian republic. Then, the didactic-pedagogical strategy that the Faculty of Philosophy and Letters of the University of Buenos Aires projected in order to address properly teaching students university students net. Finally, they translate Some thoughts.